Evaluation of the physical, chemical and mechanical properties of starch/PVA/bentonite clay films modified with glycidyl methacrylate - Vieira de Carvalho Neto, Alberto Goncalves [UNESP] (2020)
Films constituted by cassava starch, polyvinyl alcohol (PVA) and Bentonite clay (BNT) and glycerol as plasticizer were obtained using the casting method. In order to increase the compatibility of the polymers with the mineral and its hydrophobicity, they were subsequently chemically modified by replacing the hydroxyl groups with vinyls using glycidyl methacrylate (GMA). This procedure generated films with excellent water sorption stability and 15% lower water vapor permeability. This strategy also resulted in a 25% improvement in tensile strength, maintaining the same Young's modulus and slight decrease in thermal stability (onset of degradation 14 degrees C lower). The addition of BNT clay generates composite films with different mechanical, thermal and physical properties, however, there is a dependence between the amount of reinforcement and the structural distribution of the clay lamellae in the matrix. The chemical modifications were confirmed by H 1 NMR, FTIR, XRD and the films were characterized by XRD, sorption and water permeability, mechanical tests (traction, stretching and Young's modulus) and TGA. The use of 1% w / w of this reinforcement generates composites with structurally exfoliated BNT, independently of the previous modification with glycidyl methacrylate. The formulation with 5% m / m generated intercalated composite films. Any other reinforcing content exhibits agglomerated (packaged) lamellar structures. It is noteworthy that in the formulations reinforced with 1% clay, there was an improvement of about 30% in tensile strength with 60% lower water permeability, for higher clayey loads. These facts indicate that the modifications proposed in this work have generated promising properties for the production of biodegradable packaging materials.